The Greenconsumption Effect: How Using Green Products Improves Consumption Experience - Tezer, Ali; Bodur, H Onur (Journal of Consumer Research, 2020)
Abstract In many situations, consumers use green products without a deliberate choice to use or purchase the product. This research explores how using a green product (e.g., a pair of headphones made from recycled materials) influences the enjoyment of the accompanying consumption experience (e.g., listening to music), even if consumers have not deliberately chosen or purchased the product. Five experiments in actual consumption settings revealed that using a green (vs. conventional) product enhances the enjoyment of the accompanying consumption experience, referred to as the greenconsumption effect. Merely using a green product makes consumers perceive an increase in the extent to which they are valued as individuals by society, which leads to warm glow feelings, and consequently enhances the enjoyment of the accompanying consumption experience. When consumers experience low social worth, the positive effect of using green products on the accompanying consumption experience is amplified. The greenconsumption effect disappears when the negative environmental impact of the green product attribute is low. From a managerial standpoint, the current research identifies instances where brands can benefit from going green and encourages marketers, especially service providers, to promote green products that are instrumental in consumption experiences.